Brief answers to the big questions - Hawking, Stephen, 1942-2018; Redmayne, Eddie, 1982-; Thorne, Kip S.; Hawking, Lucy (London : John Murray, 2020)
"Dr. Stephen Hawking was the most renowned scientist since Einstein, known both for his groundbreaking work in physics and cosmology and for his mischievous sense of humor. He educated millions of readers about the origins of the universe and the nature of black holes, and inspired millions more by defying a terrifying early prognosis of ALS, which originally gave him only two years to live. In later life he could communicate only by using a few facial muscles, but he continued to advance his field and serve as a revered voice on social and humanitarian issues. Hawking not only unraveled some of the universe's greatest mysteries but also believed science plays a critical role in fixing problems here on Earth. Now he turns his attention to the most urgent issues facing us. Will humanity survive? Should we colonize space? Does God exist? These are just a few of the questions Hawking addresses in this wide-ranging, passionately argued final book from one of the greatest minds in history. Featuring a foreword by Eddie Redmayne, who won an Oscar playing Stephen Hawking, an introduction by Nobel Laureate Kip Thorne, and an afterword from Hawking's daughter, Lucy." --
Foreword / Eddie Redmayne -- An introduction / Kip Thorne -- Why we must ask the big questions -- Is there a God? -- How did it all begin? -- Is there other intelligent life in the universe? -- Can we predict the future? -- What is inside a black hole? -- Is time travel possible? -- Will we survive on Earth? -- Should we colonise space? -- Will artificial intelligence outsmart us? -- How do we shape the future? -- Afterword / Lucy Hawking.
Includes index.
Keywords: Philosophische Anthropologie; Science -- Philosophy; Philosophy and science; Religion and science; Inquiry (Theory of knowledge); Science -- Miscellanea; Science -- Miscellanea; Science -- Miscellanea; SCIENCE -- Cosmology; SCIENCE -- Physics -- Astrophysics; BIOGRAPHY & AUTOBIOGRAPHY -- Personal Memoirs; Science -- Philosophy; Religion and science; Philosophy and science; Inquiry (Theory of knowledge); Science; Gottesfrage; Künstliche Intelligenz; Kosmologie; Weltall; Naturwissenschaften; Science -- Miscellanea; Miscellanea; FAQs; Miscellanea; FAQs